Swan Neck Deformity Mimicking Claw Hand Caused by Arthritis in Leprosy - Hendra Gunawan; Nia Srie Haryati; Oki Suwarsa (Karger Publishers, 2017)
Swan neck deformity is a hyperextension of the proximal interphalangeal (PIP) joints and flexion of the distal interphalangeal (DIP) joints. Claw hand is a hyperextension of the metacarpal joints and flexion of the PIP joints, accompanied by reduced motor strength. A 23-year-old female, who was released from leprosy treatment, presented with a bend of the second to fifth fingers of both hands. There was hyperextension of the PIP joints and flexion of the DIP joints from the second to fifth fingers of both hands, thickening of the ulnar nerves, and hypoesthesia without motor impairment of the fourth and fifth fingers of both hands. Radiograph examination revealed cupping of the base of the proximal phalangeal joints of the second, third, and fifth fingers of the left hand and of the second and fifth fingers of the right hand. Additionally, narrowing of the metacarpophalangeal joints of the second, third, and fifth fingers of the right hand and sclerosis of the second and fifth fingers of the right hand were also observed. Claw hand is frequently reported in leprosy, while swan neck deformity is frequently reported in rheumatoid arthritis. To our knowledge, this is the first reported case with swan neck deformity caused by arthritis in leprosy.